Correlation of Spiritual Care and Quality of Life among Institutionalized Older People - Walter Jerome Cabale; Margarette Cayetano (Bedan Research Journal, 2019)
Ensuring that Older People have good quality of life is one of the major goals of any caregiver. Caregivers, which includes nurses, must be holistic in their provision of care to meet such a goal. Since one of the dimensions of quality of life is spirituality, these researchers sought to describe if any relationship exists between the caregivers’ spiritual care practices and the quality of life of the older people in their care. Institutionalized older people were surveyed using the Nurse Spiritual Care Therapeutics scale and WHO Quality of Life for Filipino Older People to measure the spiritual care practices of caregivers and the quality of life of Older People, respectively. Results show no significant relationship between the two variables, which may be due to the fact that quality of life is composed of several dimensions, in which spirituality is only one, and is multi-factorial in nature; suggesting that quality of life is influenced by several factors and how these factors interplay ultimately determine the quality of life of Older People. The researchers recommend that a mixed-method approach be used to further understand the lack of direct relationship between the two variables. References Abbasi, M., Farahani-Nia, M., Mehrdad, N., Azamgivari, and Haghani, H. (2014). Nursing students’ spiritual well-being, spirituality and spiritual care. Iran Journal of Nursing and Midwifery Research. 2014 May-Jun; 19(3): 242-247.Almeida-Brasil, C. C., Silveira, M. R., Silva, K. R., Lima, M. G., Faria, C. D. C. de M., Cardoso, C. L., Menzel, H.-J. K., Ceccato, M. das G. B. (2017). Qualidade de vida e características associadas: aplicação do WHOQOL-BREF no contexto da Atenção Primária à Saúde. Ciência & Saúde Coletiva, 22(5), 1705-1716. doi:10.1590/1413-81232017225.20362015Bai, M., & Lazenby, M. (2015). A systematic review of associations between spiritual well-being and quality of life at the scale and factor levels in studies among patients with cancer. Journal of Palliative Medicine, 18(3), 286-298. doi:10.1089/jpm.2014.0189Baldacchino, D. R. (2006). Nursing competencies for spiritual care. Journal of Clinical Nursing, 15(7), 885-896. doi:10.1111/j.1365-2702.2006.01643.xBerman, A., and Snyder, S. (2012). Kozier & Erb’s Fundamentals of nursing: concepts, process, and practice, 9th ed. WY: Pearson Canada, A. L., Murphy, P. E., Fitchett, G., & Stein, K. (2015). Reexamining the Contributions of Faith, Meaning, and Peace to Quality of Life: a Report from the American Cancer Society’s Studies of Cancer Survivors-II (SCS-II). Annals of Behavioral Medicine, 50(1), 79-86. doi:10.1007/s12160-015-9735-yCarpenter, K., Girvin, L., Kitner, W., & Ruth-Sahd, L. A. (2008). Spirituality. dimensions of critical care nursing, 27(1), 16-20.doi:10.1097/01.dcc.0000304668.99121Chen, J., Lin, Y., Yan, J., Wu, Y., and Hu, R. (2018). The effects of spiritual care on quality of life and spiritual well-being among patients with terminal illness: A systematic review. Palliative Medicine, 1-13. doi: 10.1177/0269216318772267 Chen, Y.-H., Lin, L.-C., Chuang, L.-L., & Chen, M.-L. (2017). The relationship of physiopsychosocial factors and spiritual wellbeingin elderly residents: Implications for evidence-based practice. Worldviews on Evidence-Based Nursing, 14(6), 484-491. doi:10.1111/wvn.12243Counted, V., Possamai, A., & Meade, T. (2018). Relational spirituality and quality of life 2007 to 2017: an integrative research review.health and quality of life outcomes, 16(1). doi:10.1186/s12955-018-0895-xCrimmins, EM (2015). Lifespan and healthspan: Past, preseny, promise. Gerontologist, 55(6):901-11. doi: 10.1093/geront/gnv130De Araújo, A. A., Rebouças Barbosa, R. A. S., de Menezes, M. S. S., de Medeiros, I. I. F., de Araújo, R. F., & de Medeiros, C. A. C. X. (2015). Quality of life, family support, and comorbidities in institutionalized elders with and without symptoms of depression. Psychiatric Quarterly, 87(2), 281-291. doi:10.1007/s11126-015-9386-yDe Almeida Moreira, P., Roriz, A. K. C., Mello, A. L., & Ramos, L. B. (2015). Quality of life of institutionalized elderly in Brazil. SocialIndicators Research, 126(1), 187-197. doi:10.1007/s11205-015-0888-7Fernández-Mayoralas, G., Rojo-Pérez, F., Martínez-Martín, P., Prieto-Flores, M.-E., Rodríguez-Blázquez, C., Martín-García, S., Rojo-Abuín, J.-M. and Forjaz, M.-J. (2015). Active ageing and quality of life: factors associated with participation in leisure activities among institutionalized older adults, with and without dementia. Aging & Mental Health, 19(11), 1031-1041. doi:10.1080/13607863.2014.996734Garcia, L.M.R., and Navarro, J.M.R. (2018). The impact of quality of life on the health of older people from a multidimensional perspective. Journal of Aging Research. 2018: 4086294. doi: 10.1155/2018/4086294Goldberg, B. (1998). Connection: an exploration of spirituality in nursing care. Journal of advanced nursing, 27(4):836-42. doi: 10.1046/j.1365-2648.1998.00596.x Haugan, G. (2014). The relationship between nurse–patient interaction and meaning-in-life in cognitively intact nursing home patients.Journal of Advanced Nursing 70(1), 107-120. doi: 10.1111/jan.12173Jacobs, J. (2009). Quality of life: what does it mean for general practice? British Journal of General Practice, 59(568), 807-808. doi:10.3399/bjgp09x472854Kalish, N. (2012). Evidence-based spiritual care: a literature review. Current Opinion Supportive and Palliative Care, 2012, 6:242-246. doi:10.1097/SPC.0b013e328353811cKhaje-Bishak, Y., Payahoo, L., Pourghasem, B., Jafarabadi, M.A. (2014). Assessing the quality of life in elderly people and related factors in Tabriz, Iran. Journal of Caring Sciences, 2014, 3(4), 257-263. doi:10.5681/jcs.2014.028Mamier, I. & Taylor, E. J. (2015). Psychometric evaluation of the nurse spiritual care therapeutics scale. Western Journal of Nursing Research. 37(5), 679-694. doi: 10.1177/0193945914530191Matos TDS, Meneguin S, Ferreira MLS, and Miot HA. (2017). Quality of life and religious-spiritual coping in palliative cancer carepatients. Rev. Latino-Am. Enfermagem; 25:e2910. doi:10.1590/1518-8345.1857.2910Parse, R. R. (Ed.). (1999). Illumination: The human becoming theory in practice and research. Boston, MA: Jones & Bartlett.Pinkas, J., Gujski, M., Humeniuk, E., Raczkiewicz, D., Bejga, P., Owoc, A., and Bojar, I. (2016). State of health and quality of life of women at advanced age. Medical Science Monitor, 2016; 22: 3095-3105. doi:10.12659/MSM.900572Şahin, Z.A., and Özdemir, F.K. (2016): Spirituality and spiritual care: A descriptive survey of nursing practices In Turkey, Contemporary Nurse. doi: 10.1080/10376178.2016.1221324Sawatzky, R. Ratner, P.A., and Chiu, L. (2005). A meta-analysis of the relationship between spirituality and quality of life. SocialIndicators Research. 72 (2) 153-188. doi: 10.1007/s11205-004-5577-xShrivastava, S.R., Shrivastava, P.S., Ramasamy, J. (2013). Role of selfcare in management of diabetes mellitus. Journal of Diabetes and Metabolic Disorder, 5;12(1):14. doi: 10.1186/2251-6581-12-14Walker, A. and Breitmaster, C. (2017). The provision of spiritual care in hospices: A study in four hospices in North Rhine-Westphalia. Journal of Religion and Health. 56(6): 2237-2250. doi: 10.1007/s10943-017-0396-yWorld Health Organization (WHO) 2012. http://apps.who.int/iris/bitstream/10665/77777/1/WHO_MSD_MER_Rev.2012.04_eng.pdf?ua=1.Willemse, S., Smeets, W., Leeuwen, E., Janssen, L., and Foudraine, N. (2017). Spiritual care in the ICU: Perspectives of Dutch intensivists, ICU nurses, and spiritual caregivers. Journal of Religion and Health. 57(2): 583-595. doi: 10.1007/s10943-017-0457-2Yousefi, H. and Abedi, H.A. (2011). Spiritual care in hospitalized patients. Iranian Journal of Nursing and Midwifery Research. Winter;16(1):125-132. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3203292/